2021
DOI: 10.3390/nu13124464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D Supplementation on Glycemic Control in Prediabetes: A Meta-Analysis

Abstract: Clinical research results of vitamin D supplementation in the improvement of prediabetes remain controversial. Accordingly, a literature search was conducted of PubMed, Embase (Ovid), and Web of Science prior to 9 November 2021. Randomized controlled studies reported that the following indicators were included: body mass index (BMI), fasting blood glucose (FBG), 2 h oral glucose tolerance test plasma glucose (2h-PG), hemoglobin A1c (HbA1c), insulin resistance by homeostasis model assessment (HOMA-IR), homeosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…It tends to increase and remains high during insulin resistance, impairing glucose tolerance. 33 Our results showed that the intervention with DOP in SD rats decreased the fasting blood glucose and improved glucose tolerance. The findings are aligns with a study showing that DOP intervention also improved pancreatic damage and metabolism disorders of bile acid and amino acid in diabetic rats.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…It tends to increase and remains high during insulin resistance, impairing glucose tolerance. 33 Our results showed that the intervention with DOP in SD rats decreased the fasting blood glucose and improved glucose tolerance. The findings are aligns with a study showing that DOP intervention also improved pancreatic damage and metabolism disorders of bile acid and amino acid in diabetic rats.…”
Section: Discussionmentioning
confidence: 49%
“…Fasting blood glucose is maintained within a lower range under normal circumstances. It tends to increase and remains high during insulin resistance, impairing glucose tolerance 33 . Our results showed that the intervention with DOP in SD rats decreased the fasting blood glucose and improved glucose tolerance.…”
Section: Discussionmentioning
confidence: 50%
“…Nonetheless, some research ndings indicate that vitamin D signi cantly lowers HbA1c in those with prediabetes or diabetes (56-58). Additionally, a number of earlier studies have demonstrated that vitamin D supplementation can lower the risk of developing diabetes in prediabetic persons (53,57,(59)(60)(61). As a result, it appears that su cient vitamin D levels have a positive impact on lowering blood sugar levels, especially in the prediabetic population.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the results of current studies were contradictory. Some studies on pre-diabetic patients ( Lemieux et al, 2019 ; Zhang et al, 2021 ) and T2DM patients ( Farrokhian et al, 2017 ; Safarpour et al, 2020 ) have shown the benefits of VDS. A meta-analysis conducted by Zhang et al reported that VDS resulted in a vast improvement in FPG, HbA1c, and FI levels in prediabetics, but not in other parameters ( Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on pre-diabetic patients ( Lemieux et al, 2019 ; Zhang et al, 2021 ) and T2DM patients ( Farrokhian et al, 2017 ; Safarpour et al, 2020 ) have shown the benefits of VDS. A meta-analysis conducted by Zhang et al reported that VDS resulted in a vast improvement in FPG, HbA1c, and FI levels in prediabetics, but not in other parameters ( Zhang et al, 2021 ). However, a meta-analysis of 23 RCTs investigating the influence of vitamin D on glycemic control in individuals with T2DM revealed no effect on FPG, HOMA-IR and HbA1c ( Krul-Poel et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%